Hannah's Heirs : the Quest for the Genetic Origins of Alzheimer's Disease. - Pollen, Daniel A. (Oxford University Press, 1996)
The internationally acclaimed story of Hannah's Heirs now resumes in this updated paperback edition with the discovery in June, 1995 of Hannah's gene--now known to account for the majority of mutations causing early onset familial Alzheimer's disease--and the equally important identification of the major genetic risk factor rendering increased susceptibility to the more frequently occurring late-onset Alzheimer's. With these recent discoveries, medical science is now poised to reach for an understanding of the causes of the various forms of Alzheimer's disease which, in turn, will inevitably l.